LAWSUITS RELATED TO DIVORCE DUE TO APOSTASY IN BITUNG RELIGIOUS COURT - Evra Willya; Nurlaila Harun; Afni Anom (State Islamic University North Sumatra, 2022)
Abstract: This study aims to analyze the considerations of judges in deciding two divorce cases due to apostasy claims including Case Number 14/Pdt.G/2019/PA.Bitg and 17/Pdt.G/2019/PA.Bitg at the Bitung Religious Court, Bitung City, North Sulawesi, Indonesia. It was conducted qualitatively through a descriptive-comparative approach with primary data obtained from informants including four judges using observation, in-depth interviews, and documentation techniques, subsequently analyzed using an inductive analysis model. Meanwhile, secondary data were retrieved from decision documents. The results showed that the judge decided Case Number 14/Pdt.G/2019/PA.Bitg in fâsakh and Case Number 17/Pdt.G/2019/PA.Bitg in ṭalâq ba‘in sughra through the consideration of the subsidiary petitum. These decisions were observed to have legal consequences on hadhânah and the right of mutual inheritance between children and parents. Abstrak: Penelitian ini bertujuan untuk menganalisis pertimbangan hakim dalam memutuskan dua perkara perceraian dengan gugatan murtad, yakni Perkara No. 14/Pdt.G/2019/PA.Bitg dan 17/Pdt.G/2019/PA.Bitg di Pengadilan Agama Bitung Pengadilan, Kota Bitung, Sulawesi Utara, Indonesia. Penelitian dilakukan secara kualitatif melalui pendekatan deskriptif-komparatif dengan data primer diperoleh dari informan meliputi empat orang hakim dengan menggunakan teknik observasi, wawancara mendalam, dan dokumentasi, selanjutnya dianalisis menggunakan model analisis induktif. Sedangkan data sekunder diperoleh dari dokumen keputusan. Hasil penelitian menunjukkan bahwa hakim dalam memutuskan dua perkara perceraian dengan gugatan murtad berdasarkan pada alat bukti dimana Perkara No. 14/Pdt.G/2019/PA.Bitg diputuskan secara fâsakh dan Perkara No. 17/Pdt.G/2019/PA.Bitg diputuskan secara ṭalâq ba’in sughra dengan menggunakan pertimbangan petitum subsider. Kedua putusan tersebut berakibat hukum pada hadhânah dan hak saling waris antara anak dan orang tua. Keywords: judge's consideration, divorce, apostasy, marriage fasâkh, ṭalâq ba'in sughra